Kinetic Study of Malathion Biosorption Using Dry Cells of an Isolated Bacillus sp. S14 - Sabo, Ibrahim Alhaji; Yahuza, Salihu; Abubakar, Abdussamad; Dan-Iya, Bilal Ibrahim (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Pesticides Pollutants are a major ecological issue because they kill organisms that are not their intended targets. Even in trace amounts, their diversity, toxicity, and durability are harmful to natural systems. High levels of malathion in the air, water, or food can make breathing difficult, tighten the chest, cause nausea, cramps, diarrhoea, watery eyes, impaired vision, salivation, perspiration, headaches, and even cause death. Two kinetic models—pseudo-1st- and pseudo-2nd order were used to examine the sorption isotherm of malathion onto Bacillus sp. S14, and they were fitted using non-linear regression. The pseudo-1st order model was found to be the best model by statistical analysis based on root-mean-square error (RMSE), adjusted coefficient of determination (adjR2), bias factor (BF), accuracy factor (AF), corrected AICc (Akaike Information Criterion), Bayesian information criterion (BIC), and Hannan-Quinn information criterion (HQC). A kinetic study employing the pseudo-1st order model at 150 PPM yielded an equilibrium sorption capacity qe of 4.19 mg/g (95% confidence interval from 4.137448 to 4.257148) and a pseudo-1st-order rate constant, k1 of 0.53. (95 percent confidence interval from 0.510371 to 0.559508). Further analysis is required to give evidence for the chemisorption mechanism commonly associated with this kinetic.